Empowerment of Aisyiyah Branch through Utilization of Home Gardens as a Living Warehouse Movement in Gelam Village, Candi District: Pemberdayaan Ranting Aisyiyah Melalui Pemanfaatan Pekarangan Rumah Sebagai Gerakan Lumbung Hidup Di Desa Gelam, Kecamatan Candi (Indonesian Journal of Cultural and Community Development, 2024)
The Living Barn Movement represents a strategic effort to enhance food security in contemporary society. In Gelam Village, the Aisyiyah service team has been entrusted with managing home gardens to actualize this movement. Despite its significance, there is limited understanding among community members regarding effective home garden management for food production. This initiative aims to empower Aisyiyah members by cultivating cassava and papaya, two crops known for their adaptability and high yield, to bolster food security. Through outreach and education on the Living Barn Movement, the service team facilitated knowledge transfer and skill development in integrated agricultural systems. This program uniquely integrates practical gardening techniques with community education to promote sustainable food practices. The findings suggest that empowering local communities through education and resource management can significantly enhance food security, encouraging similar initiatives in other regions to address food sustainability challenges.Highlights:• The initiative cultivates cassava and papaya to enhance food security for Aisyiyah members.• Outreach efforts focus on educating community members about effective home garden management.• The program promotes sustainable practices through integrated agricultural systems and skill development.Keywords: Living Barn Movement, food security, home gardens, community education, sustainable agriculture.